FEATURES OF PREPARATION FOR THE UNIFIED NATIONAL TESTING IN SMALL SCHOOLS WITHIN THE FRAMEWORK OF DISTANCE LEARNING - Useinov Б.М.; Solodovnik А.А.; Shaimerdenova М.А.; Baizhigitova Л.О. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article discusses the technology of organizing training within the elective to achieve the goals and solve the tasks set in the updated educational standard and prepare graduates for the Unified National Testing. The main objectives of the study were to study the effectiveness of testing on the basis of various online test platforms, the development of itinerary sheets and instructions for each testing site. As a result of the research, the technology of preparation for the Unified National Testing in the conditions of distance learning as part of the elective was developed. The criterion of its effectiveness was a study conducted in small schools of the North Kazakhstan region. The paper presents the results of determining the effectiveness of the use of route sheets using electronic test platforms in them, the dynamics of success in the form of diagrams. At the same time, the implementation of the study in preparation for the Unified National Testing took place both in synchronous and asynchronous distance learning formats. The results of the pedagogical experiment allow us to talk about the positive impact of the proposed technology on the final result when passing the Unified National Testing by students.